2021
DOI: 10.1039/d1qm00462j
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor based two-dimensional covalent organic frameworks for near-infrared photothermal conversion

Abstract: Two 2D COFs containing both naphthalene diimides (NDIs) as an electron acceptor (A) and triphenylamine (PT-N-COF) or triphenylbenzene (PT-B-COF) as electron donors (D) were prepared successfully. The in-plane donor and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Further, the highest-occupied molecular orbital (HOMO)–lowest-unoccupied molecular orbital (LUMO) levels of BTZ-BCA-COF and BTZ-TPA-COF were estimated to be E HOMO = −4.60 and −4.68 eV and E LUMO = −6.96 and −6.82 eV, respectively, following the equations of (HOMO = −[(e E OX – e E (Fc/Fc + ) + 4.8 V)] eV, LUMO = HOMO – E g ) (Figure S14c, Supporting Information). , Lowering of the band gap with stronger donor–acceptor interaction of the TPA (donor) moiety with Tt (acceptor) in BTZ-TPA-COF confirmed the higher charge separation efficiency than BTZ-BCA-COF . Interestingly, the finding from CV analysis corelates with the electron transfer mechanism in the synthesized COFs. , Furthermore, lowering of the HOMO–LUMO energy gap in BTZ-TPA-COF can be attributed to the red shift in UV-DRS analysis, while the CV experiment exhibited higher CT ability of BTZ-TPA-COF than BTZ-BCA-COF, which contributes to the red shift in the emission spectrum.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Further, the highest-occupied molecular orbital (HOMO)–lowest-unoccupied molecular orbital (LUMO) levels of BTZ-BCA-COF and BTZ-TPA-COF were estimated to be E HOMO = −4.60 and −4.68 eV and E LUMO = −6.96 and −6.82 eV, respectively, following the equations of (HOMO = −[(e E OX – e E (Fc/Fc + ) + 4.8 V)] eV, LUMO = HOMO – E g ) (Figure S14c, Supporting Information). , Lowering of the band gap with stronger donor–acceptor interaction of the TPA (donor) moiety with Tt (acceptor) in BTZ-TPA-COF confirmed the higher charge separation efficiency than BTZ-BCA-COF . Interestingly, the finding from CV analysis corelates with the electron transfer mechanism in the synthesized COFs. , Furthermore, lowering of the HOMO–LUMO energy gap in BTZ-TPA-COF can be attributed to the red shift in UV-DRS analysis, while the CV experiment exhibited higher CT ability of BTZ-TPA-COF than BTZ-BCA-COF, which contributes to the red shift in the emission spectrum.…”
Section: Resultsmentioning
confidence: 70%
“…32,33 Lowering of the band gap with stronger donor−acceptor interaction of the TPA (donor) moiety with Tt (acceptor) in BTZ-TPA-COF confirmed the higher charge separation efficiency than BTZ-BCA-COF. 34 Interestingly, the finding from CV analysis corelates with the electron transfer mechanism in the synthesized COFs. 35,36 Furthermore, lowering of the HOMO−LUMO energy gap in BTZ-TPA-COF can be attributed to the red shift in UV-DRS analysis, while the CV experiment exhibited higher CT ability of BTZ-TPA-COF than BTZ-BCA-COF, which contributes to the red shift in the emission spectrum.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…[43][44][45][46][47][48] Through a literature review, we found that the bottom-up design method provides great possibilities for the synthesis of new high-performance COF catalysts. 23,[49][50][51][52][53][54][55][56][57][58] As is well known, the 4,4 0 -(2,1,3-benzothiadiazole-4,7-diyl)dianiline (BTDDA) unit is currently one of the most effective electron acceptors. It can adjust the band gap and improve the charge separation and transfer properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…All of the results indicate that the photothermal properties of 1 are better than those of other reported NIR photothermal materials. , , Especially compared with that of Co-MOF in our previous work, the performance of 1 has been further improved. Comparing the crystal structure, theoretical calculation results, and EPR spectroscopy, we could determine some reasons.…”
Section: Results and Discussionmentioning
confidence: 73%